Assessing the effects of microencapsulated Lactobacillus salivarius and cowpea seed supplementation on broiler chicken growth and health status - Lefter, Nicoleta Aurelia; Gheorghe, Anca; Habeanu, Mihaela; Ciurescu, Georgeta; Dumitru, Mihaela; Untea, Arabela Elena; Vlaicu, Petru Alexandru (Frontiers in Veterinary Science, 2023)
This study aimed to assess the nutritional quality of cowpea seeds (cv. Doljana -CSD) and the impact of partially replacing soybean meal with CSD, along with the supplementation of microencapsulated Lactobacillus salivarius (LS), on broiler chicken performance at 35 days of age. A total of 432 mixed-sex Ross308 broiler chickens, one day old, were randomly assigned to four groups, with 108 birds in each group, further divided into six pens with 18 birds in each pen. The study followed a 2×2 factorial design, involving two levels of cowpea seed inclusion (CSD0 and CSD15%) and the presence or absence (Yes/No) of microencapsulated LS probiotic (0 and 1 g/kg feed). The experimental diets did not significantly impact production performance. However, the production efficiency was notably higher in the groups with LS, whether they contained CSD or not (CSD0 with LS and CSD15 with LS), compared to groups without LS (CSD0 without LS - 322.4% and CSD15 without LS -320.6%). In terms of carcass traits, the CSD15 group with LS displayed higher dressing and liver percentages compared to the other groups. Plasma profile analysis revealed significant reductions in total cholesterol and triglycerides in the CSD15 group with LS compared to the CSD0 group, regardless of LS supplementation. Moreover, the CSD15 group with LS had significantly higher levels of total protein, albumin, and calcium, along with significantly lower uric acid levels compared to the CSD0 group, irrespective of LS supplementation. Tibia bone traits and mineral content showed no significant effects. However, pH levels decreased from 6.90 in the CSD0 group without LS to 6.69 in the CSD15 group with LS supplementation. In terms of cecal microbial populations, Coliforms decreased in the CSD15 group without LS vs. the CSD15 group with LS. Significant alterations were also observed in Clostridium spp., E. coli, Enterococcus spp., and Staphylococcus spp. in the ceca and excreta of the CSD15 group with LS supplementation compared to the CSD0 group, with or without LS supplementation. Beneficial bacteria, specifically Lactobacillus spp., significantly increased in the cecal content of CSD0 and CSD15 groups with LS compared to CSD0 and CSD15 groups without LS.